Исследование структуры потока в тракте паровпуска турбины методом математического моделирования - Бабаев, Артем Иванович; Голощапов, Владимир Николаевич (НТУ "ХПИ", 2017)
В статье приводятся результаты численного исследования структуры потока в тракте, включающего регулирующий клапан, входной патрубок, сопловой сегмент. Определено, что суммарные потери располагаемой энергии при совместной работе данных элементов превышают потери при их изолированной работе. Оновной причиной увеличения потерь энергии является наличие неравномерности параметров входного потока, сформированного в предвключённом элементе проточной части.

The article presents the results of a numerical investigation of the flow pattern in the input path of turbine K-200-12.7 including control valve, inlet pipe, nozzle segment. To determine the influence of each element in the total value of the energy loss, the calculations were carried out for the flow part of separate compartments: an isolated segment of the nozzle, inlet pipe-nozzle segment and the control valve-inlet pipe-nozzle segment. Each compartment was investigated for the modes, corresponding to the flow at low, medium and high valve opening. When calculating the model, a computational grid of tetrahedral type with prismatic sublayer and SST turbulence model was used.
Investigation of the flow pattern in the inlet part of turbine using method of mathematic modelling
Keywords: регулирующий клапан; входной патрубок; сопловой сегмент; парораспределение; паровая турбина; control valve; inlet channel; nozzle segment